The Effect of Digital Literacy and Character Education on Increasing the Quality of Learning - Prabandari, Rr C Siska Wuri; Fitria, Happy; Effendi, Darwin (Yayasan Sembilan Pemuda Indonesia, 2024)
The purpose of this study was to determine the effect of digital literacy and character education on improving the quality of learning in SMP Negeri in Pangkalan Baru sub-district, Central Bangka Regency. The sample size taken was 78 teachers in Pangkalan Baru State Junior High School, Central Bangka Regency. The sampling technique was saturated sampling, where the respondents were all teachers at Pangkalan Baru SMP Negeri, Central Bangka Regency. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 80 statement items. The analysis technique used was multiple linear regression analysis. The results showed that digital literacy and character education simultaneously have a significant effect on improving the quality of learning. Second digital literacy has a significant effect on improving the quality of learning. Third, that character education has a significant effect on improving the quality of learning.